How relationship-maintenance strategies influence athlete burnout: Mediating roles of coach–athlete relationship and basic psychological needs satisfaction - Fan, Fenghui; Chen, Jinyu; Chen, Yunting; Li, Bing; Guo, Liya; Shi, Yang; Yang, Feng; Yang, Qinjun; Yang, Longfei; Ding, Cody; Shi, Huiying (Frontiers in Psychology, 2023)
Athlete burnout has many potential negative effects on athletes’ sporting performance and career. Maintaining and promoting the coach–athlete relationship to meet athletes’ basic psychological needs is one way to reduce burnout. Existing studies of how the coach–athlete relationship influences athlete burnout have mainly focused on coaches’ behavior, with little attention given to relationship-maintenance strategies and the mechanism of athlete burnout from athletes’ perspective. Through an online survey of 256 adolescent athletes, this study explores the relationship between relationship-maintenance strategies and athlete burnout, including the potential mediating effects of the coach–athlete relationship and basic psychological needs satisfaction. The results show that athletes’ relationship-maintenance strategies negatively predicted athlete burnout. Besides the direct effect, we found evidence to support three mediation paths: (1) via the coach–athlete relationship; (2) via basic psychological needs satisfaction; and (3) via both as serial mediators. These findings enhance understanding of the mechanism of athlete burnout, demonstrating the influence of factors beyond the coach’s role. The study also provides a theoretical basis for practical intervention by coaches, athletes, and sports organizations to reduce athlete burnout by focusing on athletes’ perspective.